The statistical crisis in science: how is it relevant to clinical neuropsychology?. Issue 6 (3rd October 2017) - Gelman, Andrew; Geurts, Hilde M.
Abstract: There is currently increased attention to the statistical (and replication) crisis in science. Biomedicine and social psychology have been at the heart of this crisis, but similar problems are evident in a wide range of fields. We discuss three examples of replication challenges from the field of social psychology and some proposed solutions, and then consider the applicability of these ideas to clinical neuropsychology. In addition to procedural developments such as preregistration and open data and criticism, we recommend that data be collected and analyzed with more recognition that each new study is a part of a learning process. The goal of improving neuropsychological assessment, care, and cure is too important to not take good scientific practice seriously.